Urban planning instruments for promoting social interest housing: from zoning to obligatory percentages in São Paulo, Brazil, in dialog with Bogotá, Colombia - Santoro, Paula Freire (Revista Brasileira de Estudos Urbanos e Regionais, 2015)
One of the major challenges for urban planning in Latin America is to provide low-income families with housing in areas that have an infrastructure and a good supply of jobs and services, thereby promoting diversity and equity, translated by mixing classes, races and social cohesion. This mission becomes increasingly difficult in a neoliberal capitalist context which transfers the task of providing land and housing for low-income families to the market and where the logic of such actions is based on achieving more rent from land and consequently of the holding of real estate becoming more profitable. This paper sets out to discuss two proposals for urban instruments that dialog with the production of housing through the market and guarantee of the right to the city. The first centered on the reserve of land for the production of social interest housing (HIS, in Portuguese) in the zoning by creating Special Social Interest Housing Zones (ZEIS, in Portuguese), spread throughout Brazil, and described here based on the experience of São Paulo. Or else, comparatively, classifying land to be used as a priority for social housing (vivienda de interés prioritário) widespread in Colombia, and here presented by the Bogota experience. There is another, which already has international experience and has recently been debated in Brazil, which consists of conceiving of the promotion of social interest housing policies based on the regulation of urban restructuring but experiences of this are rare in Brazil. These may be termed as inclusive housing policies. As a result, this article points out that the creation of alternative regulations has set the tone for the market to exclude itself from producing housing of social interest, and guarantees greater profitability to commercial undertakings.